To live and die in dixie eaudiobook - Andrews, Mary Kay (Callahan Garrity, 2013)
"Bright and sassy." — New York Times Book Review The second entry in the thoroughly original and witty series about Callahan Garrity in which the cleaning lady cum sleuth runs afoul of right-wing radicals and a dangerous collector when she's hired to find the valuable and controversial diary of a Civil War madam. Former Atlanta police officer Callahan is known for scrubbing all kinds of muck, but she has no idea what she's getting herself into when she is hired by Elliott Littlefield, a notorious Atlanta antiques dealer. Right from the start, Callahan's job turns into a lively quest to find a priceless Civil War diary penned by an infamous madam. Soon Callahan and her team become entangled with a motley group of Civil War collectors, right-wing extremists, and nosy teens, making the case messier and tougher to clean. The witty Callahan Garrity mysteries by Mary Kay Andrews always entertain and delight.